Pronominal System of Soikkola Ingrian: Interrogative/Relative, Indefinite, and Negative Pronouns and Their Variation - Anna Schwarz; Fedor Rozhanskiy (Linguistica Uralica)
The paper analyses several classes of pronouns in the Soikkola dialect of the Ingrian language, namely interrogative/relative, indefinite, and negative pronouns. These classes of pronouns belong to one of the most underdescribed parts of Ingrian morphology, so the main goal of the paper is descriptive. Special focus is placed on the analysis of variation within pronoun classes. While variation in interrogative/relative pronouns mostly concerns minor aspects of their formation, indefinite and negative pronouns show many competing variants. In the case of indefinite pronouns, this variation arises from indefinite suffixes with different origins and functions. Negative pronouns have another source of variation: the morphophonological processes that can occur when a pronominal stem is concatenated with the negative particle kaa/kää. In all these classes of pronouns, we usually observe idiolectal and free variation, while contextual and register variation occurs less frequently.